Biomass and biohydrogen production by unicellular green alga Chlorella vulgaris var. vulgaris TISTR 8261 using frozen food industrial wastewater - Taikhao, Samart; Phunpruch, Saranya (Asia-Pacific Journal of Science and Technology, 2022)
Biohydrogen production by green algal biomass is promising method for sustainable H2 production and bioenergy recovery. In this approach, green algae convert organic and inorganic substances (used as the sole source of carbon and electrons) in wastewater into H2. In this study, biomass and H2 production from the unicellular green alga Chlorella vulgaris var. vulgaris TISTR 8261, cultivated in frozen food industrial wastewater, was investigated. The results revealed that growth rate of algal cells cultivated in treated wastewater was significantly higher than that in untreated wastewater but lower than that in the synthetic control Tris acetate phosphate (TAP) medium. In addition, the cells grown in treated wastewater exhibited a high ability to remove nitrate, nitrite, phosphate, and sulfate from the water. Furthermore, algal cells were cultured with various concentrations of sodium acetate (0-17.4 mM); the optical density of the cultures at 750 nm increased with increase in acetate concentration. Cell growth in treated wastewater supplemented with 17.4 mM sodium acetate was similar to that in TAP medium. The highest H2 production of 12.87 ± 0.58 µmolH2 mg Chl a-1 was observed in cells incubated in treated wastewater supplemented with 17.4 mM sodium acetate; this yield was higher than that obtained from cells incubated in nitrogen-free TAP medium. The results of this study support the potential use of wastewater for biomass and biohydrogen production by C. vulgaris var. vulgaris TISTR 8261.